Needs Analysis and Innovative Implementation of Virtual Reality Learning Media Development for Earth and Solar System Topics - Nor, Muhammad; Irianti, Mitri; Z, Fakhruddin; Prastowo, Rizo Budi; Indriyani, Feni; Windi, Windi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to examine the necessity of virtual reality (VR)-based learning media for teaching Earth and Solar System content at the junior high school level. The central issue addressed is the development of innovative educational tools that incorporate VR technology to facilitate the learning of abstract scientific concepts. A quantitative approach employing a survey method was utilized, involving 80 seventh-grade students from SMP Negeri 4 Pekanbaru. Participants were selected through convenience sampling based on availability. Data were gathered using an online questionnaire distributed via Google Forms over a two-week period and analyzed descriptively. Findings revealed that 56% of students experienced difficulties in comprehending Earth and Solar System material due to its abstract nature. Furthermore, 92% expressed a strong need for learning media capable of transforming abstract content into concrete visual representations to enhance conceptual understanding. These results underscore a significant demand for VR-based instructional media in science education, particularly in topics requiring high levels of visualization. The study implies that integrating virtual reality into the classroom could effectively address existing learning barriers, increase student engagement, and support the development of a deeper understanding of scientific phenomena through immersive technological experiences.Keywords: learning media, earth, solar system, virtual reality,